Homogeneous focusing of electron bunch sequence by plasma wakefield - Lotov, K.V.; Maslov, V.I.; Onishchenko, I.N.; Svistun, O.M. (Вопросы атомной науки и техники, 2012)
The mechanism of focusing of relativistic electron bunches by plasma wakefield, in which all bunches of sequence are focused identically and uniformly, has been proposed and investigated. In this scheme of focusing it is necessary that length of each bunch should be equal to a half of wavelength, the charge of first bunch equals half of the charge of the others bunches and the distance between bunches equals 1.5 of wavelength. It is shown that in this case only 1-st bunch is in the finite longitudinal electrical wakefield Ez. Other bunches are in zero longitudinal electrical wakefield Ez= 0. The focusing radial electrical field in regions, occupied by bunches, is constant along each bunch.